Deficient t-PA Release and Elevated PA Inhibitor Levels in Patients with Spontaneous or Recurrent Deep Venous Thrombosis - Juhan-Vague, I; Valadier, J; Alessi, M C; Aillaud, M F; Ansaldi, J; Philip-Joet, C; Holvoet, P; Serradimigni, A; Collen, D (Thrombosis and Haemostasis, 1987)
The fibrinolytic system was investigated in 120 patients with spontaneous or recurrent deep vein thrombosis (DVT) without any known organic disease able to explain by itself the occurrence of a thrombosis and without any known defect of antithrombin III, Heparin Cofactor II, Protein C, or Protein S. The assays included: Euglobulin fibrinolytic activity (EFA), tissue-type plasminogen activator related antigen (t-PA-Ag) and plasminogen activator inhibitor activity (PA inhibitor), which were measured before and after 10 min of venous occlusion (V. O.). On the basis of the results, the patients could be classified in 3 groups:good responders with an at least two-fold increase of EFA after venous occlusion (n = 76), poor responders with a lesser increase of EFA due to deficient release of t-PA (n = 12), and poor responders with a normal t-PA release but an increased level of PA-Inhibitor (n = 32).The poor responders due to deficient t-PA release (10% of total) had a higher incidence of recurrence of deep vein thrombosis, than the other groups (p <0.01). An overall correlation was found between the level of PA-Inhibitor activity and the triglyceride level (r = 0.40, p <0.01), suggesting that these elevations may be due to a common cause, at least in some of the patients.It is concluded that a poor fibrinolytic response to venous occlusion occurs in 35 percent of DVT patients. Poor responders however fall into two categories, one fourth with deficient t-PA release who have a high risk for recurrent venous thrombosis, and three fourth with increased PA-Inhibitor levels which may be associated with underlying diseases also causing hypertriglyceridemia. Further elucidation of the correlation between recurrent venous thrombosis and deficient fibrinolysis is expected to result in more specific and adequate treatment and prevention of DVT.
Keywords: Tissue type plasminogen activator (t-PA); PA inhibitor; Deep venous thrombosis; Fibrinolysis